2014
DOI: 10.2991/itmr.2014.4.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Towards a B2B E-Commerce Evaluation Management Model to Assess Organizational Drivers in Hospitals

Abstract: Effective utilization of business-to-business (B2B) electronic commerce (e-commerce) in hospitals may lead to many benefits such as increased accessibility to healthcare providers, improved process efficiency, enhanced quality of healthcare services, increased responses to changes, decreased scheduling conflicts, and reduction in administrative costs. However, many hospitals have found that they have not yet fully reaped the expected benefits from their B2B e-commerce investments. Despite this, there has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 136 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…The ability of hospitals to allocate resources required to evaluate information technology have mediating effects on the relationships between other organizational drivers such as methods of evaluating information technology investments, the process of determining user information needs, the maturity of information technology, and the realization of B2B e-commerce. [ 14 ] The four main factors of human, technology, organization, and environment influence the decision-making to adopt technology and e-commerce. One should also emphasize the factor of external pressures as a vital concept that affects the adoption of technology and e-commerce in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of hospitals to allocate resources required to evaluate information technology have mediating effects on the relationships between other organizational drivers such as methods of evaluating information technology investments, the process of determining user information needs, the maturity of information technology, and the realization of B2B e-commerce. [ 14 ] The four main factors of human, technology, organization, and environment influence the decision-making to adopt technology and e-commerce. One should also emphasize the factor of external pressures as a vital concept that affects the adoption of technology and e-commerce in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…To solve these problems, researchers suggested that it is essential for decision-making and policy-making managers, especially senior IT managers of hospitals, to precisely assess all the influencing factors on B2B e-commerce investments and ensure the accurate assessment of the maturity level of information technology, the adoption of appropriate methods for the evaluation of an investment in information technology, the processes for determining user information needs, and the level of information technology evaluation resources. [ 14 15 ]…”
Section: Discussionmentioning
confidence: 99%